2010
DOI: 10.1001/jama.2010.990
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Nevirapine-Based Services to Prevent Mother-to-Child HIV Transmission in 4 African Countries

Abstract: In this random sampling of sites with services to prevent mother-to-child HIV transmission, only 51% of HIV-exposed infants received the minimal regimen of single-dose nevirapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 24 publications
4
101
0
Order By: Relevance
“…The value for PMTCT service coverage reported for Côte d'Ivoire, in the same WHO review (41%) 18 was found to be much higher than the corresponding value derived from national survey data (18%). 30,31 Fourth, the health facilities selected for detailed investigation were obtained from a list of facilities that provided a comprehensive range of PMTCT services. Our national costs may therefore be over-estimates, as they were determined on the assumption that all individuals reached by the national PMTCT programmes only attended facilities that provided such a range of services.…”
Section: Discussionmentioning
confidence: 99%
“…The value for PMTCT service coverage reported for Côte d'Ivoire, in the same WHO review (41%) 18 was found to be much higher than the corresponding value derived from national survey data (18%). 30,31 Fourth, the health facilities selected for detailed investigation were obtained from a list of facilities that provided a comprehensive range of PMTCT services. Our national costs may therefore be over-estimates, as they were determined on the assumption that all individuals reached by the national PMTCT programmes only attended facilities that provided such a range of services.…”
Section: Discussionmentioning
confidence: 99%
“…The PEARL (PMTCT effectiveness in Africa: research and linkages to care and treatment) study has shown a failure in coverage at various points along the cascade during which mother-, provider-and facility-specific factors that facilitate infection come into play. 12 Mobile phones could be used to address several of these factors. Text messages could remind pregnant women to seek antenatal care and encourage those who test positive for HIV to link to care and adhere to treatment guidelines.…”
Section: Application To Maternal and Child Healthmentioning
confidence: 99%
“…9 Option B offers all women triple therapy for the duration of pregnancy until the cessation of breast feeding for those with CD4>350 cells/mm 3 . The view that option B is superior to option A is emerging, for several reasons: 10  its simplicity for women and programmes, as option A is especially complicated and requires many regimen changes 6  option B allows more women to have sustained exposure to HAART. For those who may fall pregnant during breastfeeding, HAART allows women to survive longer, 11 which is important for survival of their children.…”
Section: Is There Really An Option For Women?mentioning
confidence: 99%